(102) Productivity in united Arab republic الانتاجية فى الجمهورية العربية المتحدة - Mohamed I. Dessouki (the institute of national planning, 2018)
This study clarifies a simple definition of "" productivity'' , showing that the main interest is to increase production through improving productivity. Also, it shows the types of productivity measures and the use of productivity indexes.